An overview of decision-making in cerebrovascular treatment strategies: Part II - Ruptured aneurysms - Georges Versyck; Johannes van Loon; Robin Lemmens; Jelle Demeestere; Lawrence Bonne; Jo P. Peluso; Steven De Vleeschouwer (Brain and Spine)
Introduction: Decision-making for the treatment of ruptured aneurysms is an intricate process, which involves several factors. There has been a rapid advancement in endovascular, but also in the surgical treating field of ruptured intracranial aneurysms, with a growing body of evidence for either treatment technique. Research question: As there is a wide variety of treatment possibilities, it can be hard to understand the intricacies which lie behind the decision-making process for a given aneurysm. Materials and methods: An overview of the most relevant literature in decision-making on ruptured intracranial aneurysms is given. Results: Different decision-altering factors were identified, which can be divided into information from the general evidence, to influential factors such as the patient's age, initial presenting status, and aneurysmal factors such as size, morphology and aneurysmal location. Discussion and conclusion: This review provides an evidence-based overview of the most pertinent literature on these different aspects of decision-making in ruptured aneurysm cases and provides some recommendations after each of these segments. As always, all different aspects of the patient and aneurysmal factors should be taken into consideration before coming to a conclusion, as to obtain the best possible result for an individual patient.